Eli Rezkallah’s “In a Parallel Universe” Photography: Attempting Reversal Gender Stereotype in Mad-Men Era Advertising - Oktaviani, Anisa Debby; Yehezkiel, Yudhistira; Pramudito, Thoby (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
Sexism and gender stereotype turns out to be political term that refers to descrimination of women in society despite their sex and gender. Thus, contexts in sexism are coming from different background and subjects. One way to express the sexism is towards advertising industry. This paper focuses on a photography work by Lebanon-based artist and photographer, named Eli Rezkallah, who made an outstanding work of recreating the advertisement picture from the mad-man era, which depicts about sexism between men and women in workforce, especially in domestic sphere. Eli Rezkallah attempted gender reversal of sexist advertisement of products in the 1950s United States. The original picture depicts feminine submission to the dominant and hegemonic masculinity. His attempt is to depict a reversed role, or in other words, female masculinity. This article analyzes the original & reversed pictures using semiotic analysis, and comes to the conclusion that the gender reversal attempt does not succeeded and does not depict female masculinity, only depicting a different form of sexism.Key words: Gender, Masculinity, Sexism, Female, Advertising